2016
DOI: 10.1016/j.envres.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution exposure and preeclampsia among US women with and without asthma

Abstract: Maternal asthma and air pollutants have been independently associated with preeclampsia but rarely studied together. Our objective was to comprehensively evaluate preeclampsia risk based on the interaction of maternal asthma and air pollutants. Preeclampsia and asthma diagnoses, demographic and clinical data came from electronic medical records for 210,508 singleton deliveries. Modified Community Multiscale Air Quality models estimated preconception, first and second trimester and whole pregnancy exposure to: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…Indeed, similar to findings by Savitz et al (26), we previously demonstrated overall null associations between exposures to air pollutants during early gestation and risk of preeclampsia among nonasthmatic women (27) as opposed to findings on GH in the current study. However, among the 17 studies included in a recent meta-analysis on air pollution in relation to pregnancy-induced hypertensive disorders (10), only 3 treated GH separately (12)(13)(14).…”
Section: Discussionsupporting
confidence: 50%
“…Indeed, similar to findings by Savitz et al (26), we previously demonstrated overall null associations between exposures to air pollutants during early gestation and risk of preeclampsia among nonasthmatic women (27) as opposed to findings on GH in the current study. However, among the 17 studies included in a recent meta-analysis on air pollution in relation to pregnancy-induced hypertensive disorders (10), only 3 treated GH separately (12)(13)(14).…”
Section: Discussionsupporting
confidence: 50%
“…Other studies stratified by various BMI categories. Analyses restricted by BMI (stratified on pre‐pregnancy BMI ≥25 kg/m 2 only and BMI ≥30 kg/m 2 ) generally yielded similar results as the main analyses, although with a loss of precision due to the smaller sample (Mendola et al, ). Rudra et al () reported no differences in models stratified by BMI status in their finding of no association of PM 2.5 with either preterm delivery or preeclampsia.…”
Section: Resultsmentioning
confidence: 59%
“…Similarly, the literature provides evidence for a combined effect of a single air pollutant and a pre‐existing chronic condition on maternal health, but the data are limited in scope. No evidence of an increase in risk of preeclampsia with increases in PM exposure was observed in a test of interaction by maternal asthmatic status (Mendola et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequences of these effects (e.g., preeclampsia or intrauterine growth restriction) have been suggested in air monitoring studies but deserve further exploration in studies with urinary biomarkers of exposure. 9, 41 …”
Section: Discussionmentioning
confidence: 99%